Incidence and impact of Textbook Outcome among patients undergoing resection of pancreatic neuroendocrine tumors: Results of the US Neuroendocrine Tumor Study Group. Issue 8 (17th March 2020) - Heidsma, Charlotte M.; Hyer, Madison; Tsilimigras, Diamantis I.; Rocha, Flavio; Abbott, Daniel E.; Fields, Ryan; Smith, Paula M.; Poultsides, George A.; Cho, Clifford; Maithel, Shishir K.; Pawlik, Timothy M.; ,
Abstract: Background and Objectives: We sought to define the incidence and impact of Textbook Outcome (TO) on disease‐free survival [DFS] among patients undergoing resection of pancreatic neuroendocrine tumors (PNET). Methods: Patients undergoing resection of a PNET between 2000 and 2016 were identified using a multi‐institutional database. TO was defined as no postoperative severe complications (Clavien‐Dindo grade ≥ III), no 90‐day mortality, no prolonged length‐of‐hospital stay (LOS) (ie, > 75th percentile), no 90‐day readmission after discharge, and R0 resection. The 5‐year DFS was calculated and the association with TO was examined. Results: Among 821 patients with a PNET, median tumor size was 2.1 cm (IQR 1.4‐14.6). Resection consisted of pancreatoduodenectomy (PD) (n = 231, 28.1%), distal pancreatectomy (DP) (n = 492, 59.9%), and enucleation (EN) (n = 98, 11.9%). Overall TO rate was 49.3% (n = 405). The incidence of TO varied by procedure type (PD: 32.5% vs DP: 56.7% vs EN: 52.0%; P < .001). After adjusting for all competing factors, achievement of a TO was independently associated with improved DFS (hazard ratio: 0.54, 95% CI, 0.35‐0.81; P = .003). Conclusions: Only one in two patients undergoing resection of a PNET achieved a TO, which varied markedly based on procedure type. Achievement of a TO was associated with improved DFS.